2024
DOI: 10.1111/edt.12949
|View full text |Cite
|
Sign up to set email alerts
|

Influence of COVID‐19 pandemic on mandible fracture patterns in a German cranio‐maxillofacial trauma center: PreCOVID (2019) versus IntraCOVID (2020)

Florian Dudde,
Oliver Schuck,
Johannes Schunk
et al.

Abstract: Background/AimsThe COVID‐19 (Coronavirus Disease‐2019) pandemic confronted the global healthcare system with a variety of challenges. The pandemic and the associated lockdowns also had an impact on multiple medical disciplines (i.e. delay of surgery, change of hospital admissions). The aim of this study was to analyze the impact of the COVID‐19 pandemic on mandible fracture patterns/distributions and circumstances in a German cranio‐maxillofacial trauma center.Materials and MethodsThis retrospective study comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In Germany, research showed a decrease in the frequency of mandible fractures of different fracture locations. However, an increased frequency was observed in concomitant facial soft tissue injuries and traumatic tooth loss [ 18 ]. The conclusion regarding jawbone trauma was not in agreement with our research.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, research showed a decrease in the frequency of mandible fractures of different fracture locations. However, an increased frequency was observed in concomitant facial soft tissue injuries and traumatic tooth loss [ 18 ]. The conclusion regarding jawbone trauma was not in agreement with our research.…”
Section: Discussionmentioning
confidence: 99%